Pengaruh Beban Kerja Dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada Pt. Indonesia Toshin Rubber Chemical (TRC) Industry Di Area Cikarang - Rahmadhani, Intan; Musadad, Anwar (Peneliti.net, 2024)
This research aims to find out, analyze and explain the influence of workload and job satisfaction on employee performance at PT. Indonesia Toshin Rubber Chemical Industry in the Cikarang Area. With quantitative methods and using descriptive descriptive analysis, in this research the sampling technique used non-probability sampling, namely saturated sampling with a total of 286 respondents. The data analysis technique used is to test hypotheses partially and simultaneously, testing is assisted using SPSS tools. The results of the research are that the workload at the company is considered to be good, the job satisfaction is considered to be very good and very satisfying, and the performance of the employees is considered to be very good and optimal. The partial effect of Workload has an effect of 0.511 or 51.1% and Job Satisfaction has an effect of 0.173 or 17.3% on Employee Performance. The simultaneous influence of Workload and Job Satisfaction on Employee Performance is 0.684 or 68.4%, while the remaining 0.316 or 31.6% is influenced by other variables not examined. Both perceived workload and job satisfaction have a significant effect on employee performance.